2019
DOI: 10.3390/ani9060360
|View full text |Cite
|
Sign up to set email alerts
|

Lameness in Sheltered Cows and Its Association with Cow and Shelter Attributes

Abstract: The sheltering of old, unproductive and abandoned cows in traditional cow shelters, known as gaushalas, has been practiced in India since ancient times. Cows are kept in these shelters until they die of natural causes. The welfare of the cows in these shelters was assessed through a cross-sectional study of 54 cow shelters in six states of India. A total of 1620 cows were examined to assess the prevalence of lameness in these cows, and the associated risk factors for lameness were identified through the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The limited information we do know about natural cow aging largely comes from India, as cows are considered sacred, and the slaughter of cows is illegal in many Indian states. The average age of sheltered cows, those cows that are no longer productive, is 11 years (Sharma and Phillips 2019); much higher than the averages seen in commercial farming. Unlike previous work in dairy cows (Haskell et al 2006), age was not found to be associated with increased risk of lameness in Indian sheltered cows (Sharma and Phillips 2019).…”
Section: Cowsmentioning
confidence: 88%
“…The limited information we do know about natural cow aging largely comes from India, as cows are considered sacred, and the slaughter of cows is illegal in many Indian states. The average age of sheltered cows, those cows that are no longer productive, is 11 years (Sharma and Phillips 2019); much higher than the averages seen in commercial farming. Unlike previous work in dairy cows (Haskell et al 2006), age was not found to be associated with increased risk of lameness in Indian sheltered cows (Sharma and Phillips 2019).…”
Section: Cowsmentioning
confidence: 88%
“…Table 1 displays seven ABMs concerning the comfort principle, reported in 25 papers deriving from studies carried out in all continents, and the evaluations were mainly carried out on dairy cows and by direct assessment. Most of authors evaluated cleanliness as yes-no binary rating, while only two [26,27] preferred to consider the animal score on a four-or five-point rating scale from clean to dirty.…”
Section: Animal-based Measures For Cattle On Extensive/pasture-based mentioning
confidence: 99%
“…In the selected papers, several types of scores were chosen to assess the BCS as a welfare indicator of grazing animals. For dairy cows, in experiments conducted in Italy and Mexico, a score of 0-2 was used, in line with the WQ assessment protocol for cattle [28,29,31,44,56], while in other countries and situations a score of 1-5 [27,33,35,57,58] or 1-10 [59] was used. Other authors [30] used a score of 1-9 for grazing beef cows.…”
Section: Animal-based Measures For Cattle On Extensive/pasture-based mentioning
confidence: 99%
“…It is mainly at the forefront, due to the increasing prevalence and because no other common dairy disease is associated with such visible symptoms of pain [ 9 , 27 , 60 , 64 ], which may be of a long-term nature. Thus, in addition to adverse effects on production, lameness is associated with pain [ 6 , 11 , 22 , 25 , 26 , 31 , 32 , 36 , 40 , 46 , 55 , 60 , 65 , 66 , 67 ] and anxiety [ 60 ]. In this case, the dairy cow cannot exhibit natural behavior [ 6 , 40 , 55 , 63 , 68 ].…”
Section: Factors Influencing the Occurrence Of Lamenessmentioning
confidence: 99%
“…Thus, in addition to adverse effects on production, lameness is associated with pain [6,11,22,25,26,31,32,36,40,46,55,60,[65][66][67] and anxiety [60]. In this case, the dairy cow cannot exhibit natural behavior [6,40,55,63,68].…”
Section: Factors Influencing the Occurrence Of Lamenessmentioning
confidence: 99%